A highly emissive AIE-active luminophore exhibiting deep-red to near-infrared piezochromism and high-quality lasing. Issue 15 (3rd April 2020) - Lv, Chunyan; Liu, Wangwang; Luo, Qing; Yi, Haiyan; Yu, Huakang; Yang, Zhongmin; Zou, Bo; Zhang, Yujian
Abstract : A HLCT-type luminophore is prepared with bright deep-red fluorescence, showing high-performance piezochromism and lasing. Abstract : Further development of high-efficiency and low-cost organic fluorescent materials is intrinsically hampered by the energy gap law and spin statistics, especially in the near-infrared (NIR) region. Here we design a novel building block with aggregation-induced emission (AIE) activity for realizing highly efficient luminophores covering the deep-red and NIR region, which originates from an increase in the orbital overlap and electron-withdrawing ability. An organic donor–acceptor molecule (BPMT ) with the building block is prepared and can readily form J-type molecular columns with multiple C–H⋯N/O interactions. Notably, such synthesized materials can emit fluorescence centered at 701 nm with extremely high photoluminescence quantum yields (PLQYs) of 48.7%. Experimental and theoretical investigations reveal that the formation of the hybridized local and charge-transfer (HLCT) state and substantial C–H⋯N/O interactions contribute to a fast radiative decay rate and a slow nonradiative decay rate, respectively, resulting in high PLQYs in the solid state covering the NIR range. Remarkably, such BPMT crystals, as a first example, reveal strong-penetrability piezochromism along with a distinct PL change from the deep-red ( λ max = 704 nm) to NIR ( λ max = 821 nm) region. Moreover, such typical AIE-active luminophores are demonstrated to be a good candidate as a lasing medium. Together with epoxy resin by a self-assembly method, a microlaser is successfully illustrated with a lasing wavelength of 735.2 nm at a threshold of 22.3 kW cm −2 . These results provide a promising approach to extend the contents of deep-red/NIR luminophores and open a new avenue to enable applications ranging from chemical sensing to lasing.